Design of reinforcement in concrete slabs - Lee, Sai Cheng. (2008)
This report presents the results of experimental study on the punching resistance near the interior column region of flat plate. Twenty-eight isolated slab-column specimens, self-supported centrally on column stubs, were tested to failure under symmetric loading on the periphery.